2022
DOI: 10.1007/s00464-022-09253-3
|View full text |Cite
|
Sign up to set email alerts
|

Is contrast-enhanced endoscopic ultrasound-guided fine needle biopsy better than conventional fine needle biopsy? A retrospective study in a medical center

Abstract: Background Contrast-enhanced endoscopic ultrasound-guided fine needle aspiration (CE-EUS-FNA) could help clinicians to precisely locate and puncture lesions, but its effect on the diagnostic yield improvement is controversial. We designed this study to observe the additional benefit of using contrast in EUS-guided tissue sampling while performing fine needle biopsy (FNB) instead of FNA, as FNB results in a higher diagnostic accuracy. Method Patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…For example, Jani et al (2019) in their study, observed that optimal attainment of tissues from the lesions depends on factors like the size of the needles caliber, the presence of cytotechnicians for a speed evaluation on sight, the valuation of the endoscopist and the manipulation techniques of the tissues [ 25 , 26 , 27 , 28 ]. Future research could look at the impact of those other factors on the EUS-FNB diagnostic yield [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jani et al (2019) in their study, observed that optimal attainment of tissues from the lesions depends on factors like the size of the needles caliber, the presence of cytotechnicians for a speed evaluation on sight, the valuation of the endoscopist and the manipulation techniques of the tissues [ 25 , 26 , 27 , 28 ]. Future research could look at the impact of those other factors on the EUS-FNB diagnostic yield [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary meta-analysis that included only six studies (among which two were retrospective) and 701 patients reported superiority for CH-EUS-FNA[ 31 ], but subsequent studies[ 23 , 26 , 32 ] did not confirm this conclusion.…”
Section: Solid Pancreatic Lesionsmentioning
confidence: 99%
“…A retrospective study using Sonazoid contrast agent and second-generation EUSFNB needles achieved 91.7% accuracy in 48 patients with CH-EUS-FNB and 90.6% accuracy in 85 patients with conventional EUS-FNB; however, there was a lower number of passes in the CH-EUS-FNB group (2.21 ± 0.68 compared to 3.64 ± 1.20)[ 32 ]. There have been no prospective studies that have compared the time needed for each type of procedure (with and without contrast), but an additional 3 to 5 min are suggested for the preparation and observation of contrast agents[ 23 , 33 ], but the lower the number of passes might compensate for this needed time[ 32 ]. Another randomized controlled trial compared the fanning technique vs contrast-enhanced guidance for EUSFNB sampling and reported no differences in the sensitivity or accuracy (98% vs 100%).…”
Section: Solid Pancreatic Lesionsmentioning
confidence: 99%
“…In a recent meta-analysis, the pooled sensitivity, specificity, and diagnostic odds ratio of CE-EUS for the differential diagnosis of PDAC were 0.91 (95% confidence interval (CI), 0.89–0.93), 0.86 (95% CI, 0.83–0.89), and 69.50 (95% CI, 48.89–98.80), respectively [ 18 ]. Although CE-EUS does not seem to have a better diagnostic yield than tissue acquisition, it may help if cytology is inconclusive [ 20 ]. Furthermore, CE-EUS can help guide tissue acquisition by targeting the most suspicious component of the lesion and avoiding necrotic areas, biopsies of which may yield inconclusive results [ 16 , 17 , 20 ].…”
Section: Eus Techniquesmentioning
confidence: 99%
“…Although CE-EUS does not seem to have a better diagnostic yield than tissue acquisition, it may help if cytology is inconclusive [ 20 ]. Furthermore, CE-EUS can help guide tissue acquisition by targeting the most suspicious component of the lesion and avoiding necrotic areas, biopsies of which may yield inconclusive results [ 16 , 17 , 20 ].…”
Section: Eus Techniquesmentioning
confidence: 99%